Aluminium ion doping mechanism of lithium thiophosphate based solid electrolytes revealed with solid-state NMR. Issue 6 (26th January 2023) - Qu, Hongtao; Wang, Yantao; Ju, Jiangwei; van Eck, Ernst R. H.; Cui, Guanglei; Kentgens, Arno P. M.
Abstract : Doping β-Li3 PS4 by adding Al2 S3 beyond solubility limit induces highly conductive Li7 P3 S11 phase and an amorphous fraction improving lithium conductivity. Abstract : We investigate the impact of Al incorporation on the structure and dynamics of Al-doped lithium thiophosphates (Li3−3 x Al x PS4 ) based on β-Li3 PS4 . 27 Al and 6 Li magic-angle spinning NMR spectra confirm that Al 3+ ions occupy octahedral sites in the structure. Quantitative analyses of 27 Al NMR spectra show that the maximum Al incorporation is x = 0.06 in Li3−3 x Al x PS4 . The ionic conductivity of β-Li3 PS4 is enhanced by over a factor 3 due to Al incorporation. Further increase of the Al doping level leads to the formation of a more complicated material consisting of multiple crystalline and distorted phases as indicated by 31 P NMR spectra and powder X-ray diffraction. Consequently, novel Li ion diffusion pathways develop leading to a very high ionic conductivity at room temperature. NMR relaxometry shows that the activation barrier for long-range Li ion diffusion in β-Li3 PS4 hardly changes upon Al incorporation, but the onset temperature for motional narrowing comes down significantly due to Al doping. The activation barrier in the subsequently formed multiphase material decreases significantly, however, indicating a different more efficient Li ion conduction pathway.